A Versatile Biosynthetic Hydrogel Platform for Engineering of Tissue Analogues. Issue 19 (12th August 2019) - Klotz, Barbara J.; Oosterhoff, Loes A.; Utomo, Lizette; Lim, Khoon S.; Vallmajo‐Martin, Queralt; Clevers, Hans; Woodfield, Tim B. F.; Rosenberg, Antoine J. W. P.; Malda, Jos; Ehrbar, Martin; Spee, Bart; Gawlitta, Debby
Abstract: For creating functional tissue analogues in tissue engineering, stem cells require very specific 3D microenvironments to thrive and mature. Demanding (stem) cell types that are used nowadays can find such an environment in a heterogeneous protein mixture with the trade name Matrigel. Several variations of synthetic hydrogel platforms composed of poly(ethylene glycol) (PEG), which are spiked with peptides, have been recently developed and shown equivalence to Matrigel for stem cell differentiation. Here a clinically relevant hydrogel platform, based on PEG and gelatin, which even outperforms Matrigel when targeting 3D prevascularized bone and liver organoid tissue engineering models is presented. The hybrid hydrogel with natural and synthetic components stimulates efficient cell differentiation, superior to Matrigel models. Furthermore, the strength of this hydrogel lies in the option to covalently incorporate unmodified proteins. These results demonstrate how a hybrid hydrogel platform with intermediate biological complexity, when compared to existing biological materials and synthetic PEG‐peptide approaches, can efficiently support tissue development from human primary cells. Abstract : Demanding cell types that are used nowadays, require specific three dimensional microenvironments to thrive. A versatile hydrogel platform, based on PEG and gelatin, which supports functional tissue engineering of divergent tissue types through incorporation of tissue‐specific elements is presented. The obtained results demonstrate how a hybrid hydrogel platform with intermediate biological complexity can efficiently support tissue development from human primary cells.